In sickness and in health—Type I interferon and the brain - Cao, Wei (Frontiers in Aging Neuroscience, 2024)
Type I interferons (IFN-I) represent a group of pleiotropic cytokines renowned for their antiviral activity and immune regulatory functions. Recent studies have unveiled a critical role of IFN-I in the brain, influencing various neurological processes and diseases. In this mini-review, I highlight recent findings on IFN-I's effects on brain aging, Alzheimer's disease (AD) progression, and central nervous system (CNS) homeostasis. The multifaceted influence of IFN-I on brain health and disease sheds light on the complex interplay between immune responses and neurological processes. Of particular interest is the cGAS-STING-IFN-I axis, which extensively participates in brain aging and various forms of neurodegeneration. Understanding the intricate role of IFN-I and its associated pathways in the CNS not only advances our comprehension of brain health and disease but also presents opportunities for developing interventions to modify the process of neurodegeneration and prevent age-related cognitive decline.